Marine Recovery of Tunnel Boring Machine from Botany Bay - S Norman (The Australasian Institute of Mining and Metallurgy, 2011)
The Water Delivery Alliance (WDA) was established to design, construct and commission the pump station and desalinated water delivery pipeline to link the desalination plant on the Kurnell Peninsula (constructed by others) with the existing distribution network at Erskineville, Sydney, Australia. The WDA consisted of McConnell Dowell Corporation Ltd (Macdow), Bovis Lend Lease Pty Ltd (BLL), Kellogg Brown and Root Pty Ltd (KBR), Worleyparsons Ltd (WOR), Environmental Resources Management Group Inc (ERM) and Sydney Water Corporation (SWC).Sydney’s Desalination Project is one of the initiatives to secure Sydney’s water supply against the effects of climate change, population growth and drought. The desalination plant, 100 per cent powered by renewable energy, can supply up to 250 million litres of water per day (mld), which is up to 15 per cent of Sydney’s water needs. The project involved the construction of an 18 km pipeline with an ultimate capacity of 500 mld to accommodate any future increase in the output of the desalination plant.The Alliance procured three full-face tunnel boring machines (TBM) from Herrenknecht AG to construct the 6.5 km of tunnel that would provide a conduit for the DN1800 welded mild steel cement mortar lined (MSCL) pipeline at a number of locations along the route. Nineteen shafts and 16 tunnels were required to complete this work.Crucially one of the TBM drives involved construction of a tunnel into Botany Bay under protected marine life habitats; enabling the connection of the MSCL water carrier pipeline into the dredged section of pipeline underwater, approximately 800 m off-shore in Botany Bay.This paper details the retrieval of the 17.4 m long TBM from the ocean floor upon completion of the Botany Bay tunnel allowing for subsequent use on the Project. Elements covered in the paper include the 835 m tunnel, design and construction techniques for the tunnel and recovery, and details of the methods used to install the DN1800 water carrier pipeline.